Integration Of Language Policy In Learning Debate Texts For Students Of Class X Sma Qonita Islamic Boarding School - Sintia, Haqsirvenny; Anwar, Miftahulkhairah; Utami, Sintowati Rini (UNIVERSITAS PAKUAN, 2025)
This study aims to: (1) determine the integration of politeness of language of grade X high school students during debate learning in class. (2) determine the factors that influence politeness of language in debate practice in grade X students of SMAIT Qonita Islamic Boarding School. (3) determine the good politeness model in learning debate texts for students of SMAIT Qonita Islamic Boarding School. The method used in this study is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which is a systematic approach to instructional development. This model was chosen because it is often used in designing effective and efficient learning. Based on this study, it is concluded that the development of a module integrated with politeness of language has a positive impact on students' communication skills and behavior. This module teaches the application of politeness and wisdom maxims in debate, which not only improves students' argumentative abilities but also their understanding of the importance of respecting the opponent's point of view. Using the ADDIE method, this study shows a significant increase in the use of politeness of language and the application of good communication principles. Learning that integrates politeness also helps shape students' characters who respect differences of opinion. Therefore, it is suggested that this approach be implemented in schools to develop effective and ethical language skills. This study contributes to the literature on language education and practical insights for educators in creating learning environments that support students' social and communication skills.